THE INFLUENCE OF FINANCIAL RATIOS ON FIRM VALUE WITH THE CSR MODERATING VARIABLE: LQ45 COMPANIES - Wisnu Yuwono; Candy Candy; Joey Joey (Islamic University of Kalimantan MAB Banjarmasin, 2024)
Economic conditions during the Covid-19 pandemic experienced a significant decline in all countries of the world, including Indonesia. Therefore, in preparing this thesis, it was discovered that the author wanted to observe all companies registered in LQ45 regarding efforts to increase firm value, especially when facing the Covid-19 pandemic in Indonesia. This research samples using companies that listed on IDX where operate in the LQ45 index during 2017-2021. This research is using panel regression method as the data analysis method. The research conducted shows that the independent variables liquidity, leverage and profitability have a significant positive effect on firm value, while the independent variables firm size and CSR have no significant effect on the dependent variable firm value.